Creating enlightened heroes : promoting empathy in 9th grade students - Nogueira, Inês Marques Guedes (2020)
According to the existing literature, the outcomes of practicing Mindfulness are important and can aid the topics taught by the Heroic Imagination Project’s (HIP) curriculum. Therefore, the objective established was to create and implement a new programme that incorporated both Mindfulness and HIP sessions. Additionally, our study aimed to explore participants’ perspectives and experiences, their changes regarding their closest relationships, as well as their school life. Thus, five participants from Form 9 volunteered to participate in the “Creating Enlightened Heroes” nine-week programme. Throughout the sessions they filled in a diary and, at the end of the programme, were asked to answer two feedback questions. Furthermore, they were then invited to participate in individual interviews. This data was then transcribed and processed utilizing Nvivo 11. The participants reported a positive overall perspective regarding the programme, mentioning several improvements in their relationships regarding their family, peers and with others in society. Moreover, it was described by the participants that the programme helped and promoted prosocial behaviours and aided them regarding their empathy. Finally, regarding participants’ anxiety, attention and concentration in their daily lives as well at school, improvements were observed.